Enhanced electrochemical catalysis performance of transitional metal electrode through defect engineering - Han, Yin (Nanyang Technological University, 2020)
The aim of this project is to evaluate the electrochemical performance of transitional metal catalyst and the effect of defect engineering on enhancing the performance of catalytic behavior of the electrode. Carbon steel will be employed as the working electrode and its ability to perform in Hydrogen Evolution Reaction (HER) will be examined by various types of electrochemical experiments, mainly Linear Sweep Voltammetry (LSV), Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS). The processing methods employed for defect engineering will mostly focus on physical deformation on material surface and sub-surface. By creating surface lattice discontinuity, bulk roughness on basal plane. optimum active site density can be achieved by controlling the process parameters for indentation and hydraulic press. The relationship of defect density and HER activity were observed and analyzed. Scanning electron microscopy (SEM) were used to study the sample surface morphology and Energy Dispersive X-ray spectroscopy (EDS) were employed to trace the elemental composition of the samples. SEM images revealed that increasing processing parameters such as quantity of dent, loading pressure has a significant impact on the sample roughness and electrochemical performance. There is a general linear trend for hydraulic pressed samples where higher load distribution leads to greater increase in active site density. However, effectiveness of processes starts to decline beyond the optimum process parameter and this is observed for both methods. X-Ray Diffractometry XRD were used to confirmed that the sample phase state of carbon steel which is 100% BCC. LSV results show that defect engineering is a promising way to increase the active sites on electrode surface, with a 409mV decrease in overpotential at 10mA⁄(cm^2 ) for 1kN1D sample and a 255mV decrease for HP8T sample. Tafel plot also revealed a low gradient for HP10T sample, indicating an overall faster reaction kinetic during electrochemical charge transfer step. CV Randles circuit result shows lowest capacitance resistance ( ct = 4.36Ω ) for HP10T sample, which further confirms the effectiveness of the electrocatalyst in terms of carrier diffusion efficiency, the smaller ct indicates faster interfacial charge transfer process during formation of double capacitance layer. Thus, the proposed defect engineering methods can be a promising way towards the development of highly functional and efficient electrocatalyst with relatively inexpensive, scalable and simple manufacturing technique.